The Role of Business Ethics and Religiosity in Student Ethical Decision Making - Jurica Lucyanda; Gunardi Endro (JFBA: Journal of Financial and Behavioural Accounting, 2021)
This research aims to investigate the role of business ethics and religiosity in student ethical decision-making. The business ethics literature explains that ethical decision-making is influenced by internal factors of an individual nature and external factors of a situational nature. This research tried to fill the gap in the previous research that has been done. This study used two independent variables: business ethics and religiosity variables, and the independent variable is ethical decision-making. This study used experimental methods to test the hypotheses. Participants involved in this study are undergraduate economics and business students from a private university in Jakarta. The data analysis technique in this study used analysis of variance (ANOVA). The result found that business ethics courses and religiosity influence the students' ethical decision-making. Moreover, the results found that the interaction of gender and religiosity did not affect students' ethical decision-making. This research contributes to behavioral research and business ethics literature, especially in ethical decision-making.